Characterizing spatio-temporal changes in benthic communities: Taxonomic and functional trajectories of intertidal assemblages in the bay of Saint-Brieuc (English Channel). (5th November 2021) - Sturbois, A.; Cormy, G.; Schaal, G.; Gauthier, O.; Ponsero, A.; Le Mao, P.; Riera, P.; Desroy, N.
Abstract: Tracking and quantifying ecological changes at large and long-term scales is a central point for monitoring and conservation issues. The Community Trajectory Analysis Framework was used in complement with classical methods to analyse and represent long-term changes in marine habitats at 42 stations in the bay of Saint-Brieuc (western English Channel), sampled in 1987, 2001 and 2019. The taxonomic and functional trajectories of intertidal benthic assemblages were studied at local and assemblage scales. Whatever the perennial contribution of dominant prevalent species at the site scale, some species were highly variable over time and space, influencing the structuration of assemblages. Taxonomic changes were not systematically associated with significant changes in the functional properties at local and community scale. The consideration of local changes and variations at the species level explained the differences in composition observed at the scale of assemblages. Observed changes mainly reflected random population dynamics of structuring prevalent species in habitat under strong natural pressures, rather than specific changes of the community. Few species reveal the long-term effect of green tides in some assemblages. Overall, this study confirms the complexity to disentangle factors of changes in the absence of a monitoring strategy specifically devoted the measurement of environmental factors and anthropogenic pressures. The study also highlights the need for the development of benthic monitoring strategies at multiple spatial and temporal scales. Graphical abstract: Image 1 Highlights: Five benthic assemblages with various dynamics were observed. Pattern of dominance of specific species dictates taxonomic trajectories. Spatio-temporal patterns in taxonomic and functional trajectories were independent. The Community Trajectory Analysis bring new perspectives to track change in marine habitats.